Советская поэзия 30-х годов: [сборник] / сост. А. М. Турков - Турков А. М. (Школьная библиотека, 1984)
Экземпляры: ЧЗ (20160504) / Инвентарный номер: 44353 / Цена: 11.00 / Авт.знак: С56 / ГРНТИ: 17 / ББК: 84.2Рос6